Starkes Mädchen, starke Stimme, viel Gefühl. Die erstaunlichen Abenteuer der Maulina Schmitt als Buch und Hörbuch in freier Lesezeit - Kruse, Iris; Terhorst , Sarah (Klangwelten für Kinder und Jugendliche. Hörmedien in ästhetischer, didaktischer und historischer Perspektive.)

Prozessgerechte Gestaltung von Werkzeugen auf Basis von Verschleißsimulationen am Beispiel des Ultraschallbondens - Eichwald, Paul

Mixed‐Valence Compounds as Polarizing Agents for Overhauser Dynamic Nuclear Polarization in Solids - Gurinov, Andrei; Sieland, Benedikt; Kuzhelev, Andrey; Elgabarty, Hossam; Kühne, Thomas; Prisner, Thomas; Paradies, Jan; Baldus, Marc; Ivanov, Konstantin L.; Pylaeva, Svetlana (Angewandte Chemie International Edition)
Keywords: General Chemistry; Catalysis

Im Modus der Anästhetik? - Vignettenbasierte Überlegungen zu lehrgangsgestütztem Anfangsunterricht - Kruse, Iris (Materialität des Schrifterwerbs. Herausforderungen für die Forschung zum Lesen- und Schreibenlernen)

SecuCheck: Engineering configurable taint analysis for software developers - Piskachev, Goran; Krishnamurthy, Ranjith; Bodden, Eric (2021 IEEE 21st International Working Conference on Source Code Analysis and Manipulation (SCAM))

Schreiben im Angesicht des Todes. Poetologien des Sterbens von 1968 bis heute - Harmening, Anda-Lisa Martha Josephine Anna

): Im Modus der Anästhetik? - Vignettenbasierte Überlegungen zu lehrgangsgestütztem Anfangsunterricht - Kruse, Iris (Materialität des Schrifterwerbs. Herausforderungen für die Forschung zum Lesen- und Schreibenlernen)

Im Modus der Anästhetik? - Vignettenbasierte Überlegungen zu lehrgangsgestütztem Anfangsunterricht. - Kruse, Iris (Materialität des Schrifterwerbs. Herausforderungen für die Forschung zum Lesen- und Schreibenlernen)

Neurocognitive and Neurophysiological Functions Related to ACL Injury: A Framework for Neurocognitive Approaches in Rehabilitation and Return-to-Sports Tests - Piskin, Daghan; Benjaminse, Anne; Dimitrakis, Panagiotis; Gokeler, Alli (Sports Health: A Multidisciplinary Approach)
Context: Only 55% of the athletes return to competitive sports after an anterior cruciate ligament (ACL) injury. Athletes younger than 25 years who return to sports have a second injury rate of 23%. There may be a mismatch between rehabilitation contents and the demands an athlete faces after returning to sports. Current return-to-sports (RTS) tests utilize closed and predictable motor skills; however, demands on the field are different. Neurocognitive functions are essential to manage dynamic sport situations and may fluctuate after peripheral injuries. Most RTS and rehabilitation paradigms appear to lack this aspect, which might be linked to increased risk of second injury. Objective: This systematic and scoping review aims to map existing evidence about neurocognitive and neurophysiological functions in athletes, which could be linked to ACL injury in an integrated fashion and bring an extensive perspective to assessment and rehabilitation approaches. Data Sources: PubMed and Cochrane databases were searched to identify relevant studies published between 2005 and 2020 using the keywords ACL, brain, cortical, neuroplasticity, cognitive, cognition, neurocognition, and athletes. Study Selection: Studies investigating either neurocognitive or neurophysiological functions in athletes and linking these to ACL injury regardless of their design and technique were included. Study Design: Systematic review. Level of Evidence: Level 3. Data Extraction: The demographic, temporal, neurological, and behavioral data revealing possible injury-related aspects were extracted and summarized. Results: A total of 16 studies were included in this review. Deficits in different neurocognitive domains and changes in neurophysiological functions could be a predisposing risk factor for, or a consequence caused by, ACL injuries. Conclusion: Clinicians should view ACL injuries not only as a musculoskeletal but also as a neural lesion with neurocognitive and neurophysiological aspects. Rehabilitation and RTS paradigms should consider these changes for assessment and interventions after injury.
Keywords: Physical Therapy; Sports Therapy and Rehabilitation; Orthopedics and Sports Medicine

Anterior cruciate ligament injury mechanisms through a neurocognition lens: implications for injury screening - Gokeler, Alli; Benjaminse, Anne; Della Villa, Francesco; Tosarelli, Fillippo; Verhagen, Evert; Baumeister, Jochen (BMJ Open Sport & Exercise Medicine)
Athletes in team sports have to quickly visually perceive actions of opponents and teammates while executing their own movements. These continuous actions are performed under time pressure and may contribute to a non-contact ACL injury. However, ACL injury screening and prevention programmes are primarily based on standardised movements in a predictable environment. The sports environment provides much greater cognitive demand because athletes must attend their attention to numerous external stimuli and inhibit impulsive actions. Any deficit or delay in attentional processing may contribute to an inability to correct potential errors in complex coordination, resulting in knee positions that increase the ACL injury risk. In this viewpoint, we advocate that ACL injury screening should include the sports specific neurocognitive demands.
Keywords: Physical Therapy; Sports Therapy and Rehabilitation; Orthopedics and Sports Medicine